Statin Intolerance: the Clinician's Perspective - Stulc, Tomáš; Ceška, Richard; Gotto, Antonio M (Current atherosclerosis reports, 2015)
Muscle problems and other adverse symptoms associated with statin use are frequent reasons for non-adherence and discontinuation of statin therapy, which results in inadequate control of hyperlipidemia and increased cardiovascular risk. However, most patients who experience adverse symptoms during statin use are able to tolerate at least some degree of statin therapy. Given the profound cardiovascular benefits derived from statins, an adequate practical approach to statin intolerance is, therefore, of great clinical importance. Statin intolerance can be defined as the occurrence of myalgia or other adverse symptoms that are attributed to statin therapy and that lead to its discontinuation. In reality, these symptoms are actually unrelated to statin use in many patients, especially in those with atypical presentations following long periods of treatment. Thus, the first step in approaching patients with adverse symptoms during the course of statin therapy is identification of those patients for whom true statin intolerance is unlikely, since most of these patients would probably be capable of tolerating adequate statin therapy. In patients with statin intolerance, an altered dosing regimen of very low doses of statins should be attempted and, if tolerated, should gradually be increased to achieve the highest tolerable doses. In addition, other lipid-lowering drugs may be needed, either in combination with statins, or alone, if statins are not tolerated at all. Stringent control of other risk factors can aid in reducing cardiovascular risk if attaining lipid treatment goals proves difficult.
Keywords: Low-dose statin therapy; myalgie; Hyperlipidemias; Cardiovascular Diseases; rizikové faktory; Statin; Statin intolerance; Humans; lidé; statiny; tolerance léku; Drug Tolerance; Risk Factors; Muscle side effects; Myalgia; kardiovaskulární nemoci; hyperlipidemie; Hydroxymethylglutaryl-CoA Reductase Inhibitors